ANALISIS METAFORIS DALAM LIRIK LAGU GALLAGHER BROTHERS: STUDI SEMANTIK: Metaphorical Analysis in the Song Lyrics - lingga, thomson (English Literature Study Program of Universitas Kebangsaan Republik Indonesia, 2024)
The study, entitled